Temperament effects on performance and adaptability of Nellore young bulls to the feedlot environment - Braga, J. S. [UNESP] (2018)
The aim of this study was to evaluate the effects of temperament on cattle performance and adaptability to the feedlot environment, when kept under three space allowances (6, 12 and 24 m(2)/animal). Temperament of 1,350 Nellore young bulls (pure and crossbred) were assessed by the flight speed (FS) test on days 0 (FS0), 35 (FS35) and 87 (FSfin) in the feedlot, and the differences between FSfin and FS0 (Delta FS) were calculated. Three classes of flight speed were defined (calm, intermediate and reactive) for FS0 (FSC0) and FSfin (FSCfin). Performance was assessed by recording body weights on days 0, 35 and 87 (BW0, BW35 and BWfin, respectively), average daily gains between days 0 and 35, and 0 and 87 (ADG(0-35) and ADG(0-fin), respectively), and hot carcass weight (HCW). Adrenal glands of a subset of 270 animals were collected to measure their weight (WEIGHT), and cortical (COA) and medullary (MEA) areas. Spearman's coefficients of correlation were estimated to assess the relationships between FS test results over time. General linear mixed model with Proc MIXED of SAS was used in all other analyses, and a repeated measures modelling was used for FS, except for Delta FS. For FS analysis the model included the fixed effects of space allowance, days in feedlot and 2-way interaction. For Delta FS analysis only space allowance was included. Growth performance and adrenal gland variables were analyzed considering the fixed effects of space allowance, flight speed classes (for FSC0 and FSCfin, separately) and 2-way interaction in the model. In all models, BW0 was fitted as a covariate. Means comparisons between FS classes were corrected by Tukey adjustment. Significant and positive correlations were found between all FS test values, which decreased over time in all feedlot space allowances (p < 0.01). Calm animals showed higher (p < 0.05) ADG(0-35), BW35 and BWfin means than intermediate and reactive ones, and also produced heavier carcasses at the end of the finishing period (p < 0.05). A significant effect of the interaction between FSCfin and space allowance was found for ADG(0-fin) showing that only when kept at 12m(2) of space allowance, reactive animals had lower (p < 0.05) growth performance than calm ones. Reactive cattle (FSC0) had greater COA and heavier WEIGHT (p = 0.01, for both) than calm and intermediate ones. Based on our results, it can be concluded that calm animals show better performance in the feedlot, regardless of the space provided to them in the pen, given their greater adaptability to feedlot conditions.